Implementasi Aliran Pragmatisme dalam Praktik Pembelajaran Abad - 21 - Masnor Maltufah; Nur Ayisa Rosyida; Trio Supriyanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research uses a qualitative approach with a library research method, focusing on the development of pragmatic thinking in Western and Islamic traditions and its contribution to contemporary education. Data were obtained through literature reviews from books, scientific journals, and previous research results. Data analysis was conducted using content analysis techniques to identify similarities and differences in Western and Islamic pragmatic thinking. The results of the study indicate that Western pragmatism developed through Peirce, James, and Dewey, who emphasized truth based on practical consequences and usefulness in life. Islamic pragmatism, although not explicit, is reflected in the thoughts of Al-Ghazali and Ibn Khaldun, who combine revelation with empirical experience and public welfare. The contribution of pragmatism to contemporary education includes: (1) educational goals oriented towards social experiences and problem-solving; (2) the position of students as active subjects with growth capacity; (3) curriculum development that is flexible, experience-based, and adaptive to social changes. this research states that Western and Islamic pragmatism both provide important contributions to contemporary education, shifting the focus from knowledge transfer to the development of competencies and characters that are relevant.